Effect of MK-801 and Clozapine on the Proteome of Cultured Human Oligodendrocytes - Cassoli, Juliana S.; Iwata, Keiko; Steiner, Johann; Guest, Paul C.; Turck, Christoph W.; Nascimento, Juliana M.; Martins-de-Souza, Daniel (Frontiers in Cellular Neuroscience, 2016)
Separate lines of evidence have demonstrated the involvement of NMDA receptor and oligodendrocyte dysfunctions in schizophrenia. Here we have carried out shotgun mass spectrometry proteome analysis of oligodendrocytes treated with the NMDA receptor antagonist MK-801 to gain potential insights into these effects at the molecular level. The MK-801 treatment led to alterations in the levels of 68 proteins, which are associated with seven distinct biological processes. Most of these proteins are involved in energy metabolism and many have been found to be dysregulated in previous proteomic studies of post-mortem brain tissues from schizophrenia patients. Finally, addition of the antipsychotic clozapine to MK-801-treated oligodendrocyte cultures resulted in changes in the levels of 45 proteins and treatment with clozapine alone altered 122 proteins and many of these showed opposite changes to the MK-801effects. Therefore, these proteins and the associated energy metabolism pathways should be explored as potential biomarkers of antipsychotic efficacy. In conclusion, MK-801 treatment of oligodendrocytes may provide a useful model for testing the efficacy of novel treatment approaches.